Efektifitas Penggunaan Media Dalam Pemberian Konseling Gizi Untuk Peningkatan Hemoglobin - Intan Sari; Rahayu Khairiah (Peneliti.net, 2022)
Other effects of anemia that can occur in pregnant women are experiencing prematurity, low birth weight, postpartum hemorrhage, maternal death, cesarean delivery and mental development of children. The purpose of this study was to determine the effectiveness of the use of media in providing nutritional counseling to increase hemoglobin. The research design used in this study is the case control method. The target population in this study were all pregnant women who had their pregnancy checked at the midwife's practice during the time the researchers took data, namely 50 pregnant women and the samples taken in this study were 50 respondents. The analysis used is univariate analysis and bivariate analysis using the Wilcoxon test. The results showed that in the intervention group before counseling Hb did not increase by 14 (56%) respondents and after counseling Hb increased by 20 (80%) respondents. In the control group, the pretest Hb increased by 13 (52%) respondents and the posttest increased to 16 (64%) respondents. The results of the Wilcoxon test analysis showed that there was an effect of providing nutritional counseling for pregnant women on increasing hemoglobin levels of pregnant women with a p value of 0.016. It is recommended that health workers, especially midwives, always provide nutrition-related counseling, given the importance of maintaining nutrition in pregnant women to reduce the risks that may occur during pregnancy